Clinical and cost effectiveness of hexaminolevulinate-guided blue-light cystoscopy: evidence review and updated expert recommendations - Witjes, J Alfred; Babjuk, Marek; Gontero, Paolo; Jacqmin, Didier; Karl, Alexander; Kruck, Stephan; Mariappan, Paramananthan; Palou Redorta, Juan; Stenzl, Arnulf; van Velthoven, Roland; Zaak, Dirk (European urology, 2014)
CONTEXT: Non-muscle-invasive bladder cancer (NMIBC) is associated with a high recurrence risk, partly because of the persistence of lesions following transurethral resection of bladder tumour (TURBT) due to the presence of multiple lesions and the difficulty in identifying the exact extent and location of tumours using standard white-light cystoscopy (WLC). Hexaminolevulinate (HAL) is an optical-imaging agent used with blue-light cystoscopy (BLC) in NMIBC diagnosis. Increasing evidence from long-term follow-up confirms the benefits of BLC over WLC in terms of increased detection and reduced recurrence rates. OBJECTIVE: To provide updated expert guidance on the optimal use of HAL-guided cystoscopy in clinical practice to improve management of patients with NMIBC, based on a review of the most recent data on clinical and cost effectiveness and expert input. EVIDENCE ACQUISITION: PubMed and conference searches, supplemented by personal experience. EVIDENCE SYNTHESIS: Based on published data, it is recommended that BLC be used for all patients at initial TURBT to increase lesion detection and improve resection quality, thereby reducing recurrence and improving outcomes for patients. BLC is particularly useful in patients with abnormal urine cytology but no evidence of lesions on WLC, as it can detect carcinoma in situ that is difficult to visualise on WLC. In addition, personal experience of the authors indicates that HAL-guided BLC can be used as part of routine inpatient cystoscopic assessment following initial TURBT to confirm the efficacy of treatment and to identify any previously missed or recurrent tumours. Health economic modelling indicates that the use of HAL to assist primary TURBT is no more expensive than WLC alone and will result in improved quality-adjusted life-years and reduced costs over time. CONCLUSIONS: HAL-guided BLC is a clinically effective and cost-effective tool for improving NMIBC detection and management, thereby reducing the burden of disease for patients and the health care system. PATIENT SUMMARY: Blue-light cystoscopy (BLC) helps the urologist identify bladder tumours that may be difficult to see using standard white-light cystoscopy (WLC). As a result, the amount of tumour that is surgically removed is increased, and the risk of tumour recurrence is reduced. Although use of BLC means that the initial operation costs more than it would if only WLC were used, over time the total costs of managing bladder cancer are reduced because patients do not need as many additional operations for recurrent tumours.
Keywords: kvalita života; Time Factors; ekonomické modely; Predictive Value of Tests; Disease Progression; nádory močového měchýře; Bladder cancer; cystoskopie; Treatment Outcome; Cystectomy; Quality-Adjusted Life Years; Aminolevulinic Acid; reziduální nádor; Neoplasm Invasiveness; Cystoscopy; invazivní růst nádoru; přežití bez známek nemoci; Health Care Costs; Disease-Free Survival; Hexaminolevulinate; náklady na zdravotní péči; časové faktory; Cost effectiveness; kvalitativně upravené roky života; Recurrence; prediktivní hodnota testů; lokální recidiva nádoru; Quality of Life; analýza nákladů a výnosů; Urinary Bladder Neoplasms; Fluorescence cystoscopy; výsledek terapie; cystektomie; Models, Economic; lidé; Humans; Neoplasm Recurrence, Local; Neoplasm, Residual; Cost-Benefit Analysis; kyselina aminolevulová; Quality-adjusted life-years; progrese nemoci